Ossification of yellow ligament-lesser known common cause of thoracic myelopathy in Indian subcontinent treated surgically - Nair, Vishnu; Shetty, Abhijith; Kundnani, Vishal; Jain, Mukul; Chodavadiya, Sunil (International Journal of Research in Orthopaedics, 2023)
Background: To undertake a study which outlines the clinical and radiological features of ossification of yellow ligament (OYL) causing thoracic myelopathy (TM) in Indian subcontinent, to assess the outcomes of surgical resection of yellow ligament and compare different preoperative factors that contribute to be a risk factor in the overall post-surgical recovery rates (RR). Methods: A retrospective analysis of prospectively collected data from a cohort of 45 patients who visited our spine OPD from January 2012 to December 2019 who underwent surgical decompression for TM due to OYL was studied. The surgical outcomes and RR were calculated, compared and pre operative risk factors which could possibly be involved in giving poorer RR were analysed. Results: Our study included 45 patients who underwent surgical resection of OYL for TM. On comparison of post operative improvement in myelopathic symptoms, pre-operative mJOA score of 4.56 had increased significantly to 7.83 at 2 years follow up. While the majority (80%) of patients had an excellent and good recovery rate while 16% of patients had a fair recovery rate and 4% had no change at all in comparison to pre-operative mJOA scores. Preoperative risk factors for poor outcomes were also analysed. Conclusions: Early and timely before the onset or progression of any neurologic involvement. The pre operative risk factors which could give guarded prognosis and lower RR are, the presence of intramedullary signal changes (myelomalacia), >6-10 months of progressive pre operative symptoms and an mJOA<5.